Pokot pastoralism : environmental change and socio-economic transformation in north-west Kenya - Vehrs, Hauke-Peter (Future rural Africa, 2022)
Examines how pastoral peoples imagine, or even design, their futures under the pressure of changing environments and large-scale government projects.